2006
DOI: 10.1116/1.2208994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular environments on the electrical switching with memory of nitro-containing OPEs

Abstract: An oligo͑phenylene ethynylene͒ ͑OPE͒ molecule with a nitro side group has exhibited electrical switching with memory and thus has potential for use in molecular electronic devices. However, different research groups have reported different electrical behaviors for this molecule. In addition to variations among test structures, differences in local molecular environments could be partially responsible for the differences in the reported results. Thus, we tested four variations of a nitro-OPE/ dodecanethiol mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These experiments address monolayers of self-assembled molecules, where intermolecular interactions are present, rather than isolated molecules. 13,14 This is especially true for OPE thiols and derivatives such as the nitroOPE considered here, which assembles in highly ordered patterns with typical domains of about 100 Å. 15 Therefore, a two-dimensional ͑2D͒ model is more suitable for comparison to experimental settings rather than a 1D one, in the sense that they include the effect of a single molecule surrounded by neighboring ones.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments address monolayers of self-assembled molecules, where intermolecular interactions are present, rather than isolated molecules. 13,14 This is especially true for OPE thiols and derivatives such as the nitroOPE considered here, which assembles in highly ordered patterns with typical domains of about 100 Å. 15 Therefore, a two-dimensional ͑2D͒ model is more suitable for comparison to experimental settings rather than a 1D one, in the sense that they include the effect of a single molecule surrounded by neighboring ones.…”
Section: Introductionmentioning
confidence: 99%
“…Given sufficient trace/retrace stability, hysteresis is a form of two‐terminal bias switching, but to translate it into a memory effect, the state of a static, two‐terminal junction must be switched reversibly between at least two conductance states in operando. To characterize the memory effects of metal/SAM//EGaIn junctions, we performed write operations (W) by applying a −1.50 V bias, which puts the junction in the high‐conductance ON state, and erase operations (E) by applying 1.00 V, which puts it in the low‐conductance OFF state.…”
Section: Figurementioning
confidence: 99%
“…Such a hybrid design paradigm would be able to take advantage of the best that each technology has to offer [24,30]. Yet, most of the experimental research and development in this relatively new field has involved individual "test devices" that use processes that increase the ease and effectiveness of achieving and evaluating molecule-dependent transport [1][2][3][4][5][6]8,[11][12][13][14][16][17][18]20,21,[27][28][29], but in many cases disregard integration potential. Additionally, most of the device characterization that has been performed has been limited to individual external probing methods, rather than coherent characterization in a circuit environment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most of the device characterization that has been performed has been limited to individual external probing methods, rather than coherent characterization in a circuit environment. This is true even though the leading research in molecular electronics has shown that the devices are so environmentally sensitive that minor changes can drastically alter their electrical behaviors [4,8,18,23,26]. Thus, the development of CMOS compatible molecular electronic devices that can be characterized on-chip is essential to the realization of hybrid CMOS-molecular systems.…”
Section: Introductionmentioning
confidence: 99%